Networking agricultural policy in the region : advancing the CaRAPN Network (2010)
Provides brief information on the focus of the Caribbean Regional Agricultural Policy Network (CaRAPN), a platform established in 2003 for stakeholders to network, generate and share expertise and information products, and communicate in order to improve awareness of and participation in the agricultural policy process at national and regional levels.
Keywords: AGRICULTURAL POLICY